Meningkatkan Hasil Belajar Mata Pelajaran Seni Budaya Dengan Menggunakan Model Problem Based Learning PBL Peserta Didik Kelas X Perhotelan M1 SMK Negeri 3 Denpasar - I Ketut Muada; Maha Dewi Kusuma Wardani; I Gusti Ayu Putu Astini (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine the learning outcomes of class This research method uses Classroom Action Research which is carried out in two cycles with each cycle consisting of planning, implementation, action, observation and reflection. The subjects of this research were class This is proven by the increase in student learning outcomes in cycle I and cycle II. In cycle I the number of students who completed it was 22 people (68.78%) with an average student learning outcome score reaching 68.78. 68.78% who still do not meet the completeness of the specified value, namely 75% of the total number of students. Meanwhile, in cycle II the number of students who completed increased by 37 students or 100% with the average score for each student being 78.78. Based on the results of this research, it can be concluded that implementing the Problem Based Learning (PBL) learning model can improve the learning outcomes of Class X M1 Hospitality students at SMK Negeri 3 Denpasar.